Interspecific competition between larval stages of Aedes aegypti and Anopheles stephensi - S Haq; Gaurav Kumar; Ramesh C Dhiman (Journal of Vector Borne Diseases, 2019)
Background & objectives: Interspecific competition occurs between members of two or more different species and can often have an influence on mosquito populations. Both Aedes aegypti and Anopheles stepehensi are container breeding mosquitoes and co-exist which may result in larval competition. In this study, interspecific competition between the above two species has been monitored under the laboratory conditions. Methods: Three sets of experiments were conducted with different stages of Ae. aegypti and An. stephensi larvae. First two experiments were set up with I/II instar and III/IV instar larvae of Ae. aegypti and An. stephensi respectively in the ratios of 20:20, 20:40 and 40:20 in plastic bowls. For third set of experiment 20 IV instar larvae of Ae. aegypti were put with equal number of I instar larvae of An. stephensi. Results: In the presence of food, 12.5–15 % mortality was recorded in I/II stage larvae of Ae. aegypti while in An. stephensi mortality ranged from 21–55%. Pupation commenced from Day 6 onwards in Ae. aegypti while in An. stephensi it commenced from Day 11 onwards. In the absence of food, there was no pupation in both the species but Ae. aegypti survived up to longer duration (7.5–18.5 days with 50% mortality) in comparison to An. stephensi (2–7 days with 50% mortality). When younger stages of An. stephensi (I/II) were put together with older stages of Ae. aegypti (III/IV) in the presence of food, pupation was completed in 85% Ae. aegypti population while there was 100% mortality in An. stephensi population. Interpretation & conclusion: The better survival and development of Ae. aegypti than An. stephensi under the same conditions exhibits interspecies competition showing competitive advantage of Ae. aegypti over An. stephensi. Further research is required to have a thorough understanding of the interaction between these two container inhabiting mosquito species in the nature.